Optimizing students’ mathematical problem-solving abilities through geoboard-assisted didactic design on triangular number pattern material - Isnawan, Muhamad Galang; Sudirman, Sudirman; Sukarma, I Ketut; Wahyuni, Fitry; Alsulami, Naif Mastoor (Mahesa Research Center, 2023)
The research aimed to optimize students’ mathematical solving abilities through the implementation of a didactic design developed based on lesson study activities on triangular number patterns. The research design used was didactical design research. Participants in the study were 10 students (12–15 years old) at a junior high school in Mataram, Indonesia. The researcher was the main instrument, with several additional instruments, one of which was the didactic hypothesis design. The data were analyzed using qualitative analysis. The research results revealed an increase in students’ mathematical problem-solving abilities during the implementation of didactic design on triangular number pattern material. However, the increase that occurred was less than optimal. This increase resulted from the didactic design encouraging students to use Quizizz, geoboards, and inspirational videos to solve problems. However, when watching inspirational videos and Quizizz, there were problems, such as an unstable internet connection, so activities that should have been done in groups were done collectively for one class.